Α‐Defensins partially protect human neutrophils against Panton‐Valentine leukocidin produced by Staphylococcus aureus. (1st August 2015) - Cardot‐Martin, E.; Casalegno, J.S.; Badiou, C.; Dauwalder, O.; Keller, D.; Prévost, G.; Rieg, S.; Kern, W.V.; Cuerq, C.; Etienne, J.; Vandenesch, F.; Lina, G.; et al.
Abstract : Abstract: α ‐Defensins produced by neutrophils are important effector molecules of the innate immune system. In addition to their microbicidal effects, α ‐defensins have the ability to neutralize bacterial toxins. Panton‐Valentine leukocidin (PVL) is the hallmark of community‐acquired methicillin‐resistant Staphylococcus aureus. Staphylococcus aureus that produce PVL are responsible for severe diseases, including necrotizing pneumonia. Polymorphonuclear neutrophils (PMNs) are the target cells of PVL action. The goal of this study was to elucidate the effect of a group of α ‐defensins known as the human neutrophil peptides (HNPs) on the interactions between LukS‐PV and LukF‐PV, which compose PVL, and human PMNs. We observed that HNPs bound to both subunits of PVL and significantly decreased PVL pore formation in PMNs, with a maximum inhibition of 27%. When various HNP molecules were tested individually under the same conditions, we observed that HNP3, but not HNP1 or 2, decreased pore formation. Similarly, HNP3 significantly decreased PVL‐induced PMN lysis, with a maximum inhibition of 31%. Interestingly, HNPs did not affect LukS‐PV LukF‐PV oligomerization, LukS‐PV LukF‐PV binding to PMNs or calcium influx induced by PVL in PMNs. Our results suggest that HNP3 partially protects neutrophils against PVL by interfering with the conformational changes of PVL required to form a functional pore. Significance and Impact of the Study: Panton‐Valentine leukocidin (PVL) is a pore‐forming toxin produced by Staphylococcus aureus, responsible for neutrophil damage and key player of severe staphylococcal diseases. Antimicrobial peptides produced by neutrophils (HNP1–3) neutralize several other bacterial cytotoxins. We examined the impact of human neutrophil peptides (HNPs) on PVL cytotoxicity against human neutrophils and we found that HNPs bind to both LukS and LukF components of PVL, thereby inhibiting pore formation and neutrophil lysis. Our results suggest that HNP3 may impair PVL conformational changes required to form a functional pore and provide insight into the pathogenesis of PVL‐related staphylococcal infection, with potential impact on the disease outcome.